Ночь летающих гробов: повесть / Э. Н. Веркин - Веркин Эдуард Николаевич (Кошмарики, 2006)
Экземпляры: Д. О. (20240523) / Инвентарный номер: 39946 / Цена: 38.60 / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: В 32 / ББК: 84(2Рос-Рус)6-4